2015
DOI: 10.1080/07315724.2014.950391
|View full text |Cite
|
Sign up to set email alerts
|

ConsumingLentinula edodes(Shiitake) Mushrooms Daily Improves Human Immunity: A Randomized Dietary Intervention in Healthy Young Adults

Abstract: Regular L. edodes consumption resulted in improved immunity, as seen by improved cell proliferation and activation and increased sIgA production. The changes observed in cytokine and serum CRP levels suggest that these improvements occurred under conditions that were less inflammatory than those that existed before consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 28 publications
1
52
0
2
Order By: Relevance
“…Other Nutraceuticals. Foods that contain nutrients that may help to boost immune function include Shiitake mushrooms (Dai et al 2015;Feeney et al 2014), Reishi mushrooms (Sanodiya et al 2009), aged garlic (Percival 2016), and echinacea (Block and Mead 2003;Karsch-Volk et al 2014). Besides vitamin D (the most important of all nutraceuticals for immune function), other vitamins that strengthen immunity include vitamin C and vitamin E (De la Fuente et al 1998;Moriguchi and Muraga 2000).…”
Section: Pay Attention To Physical Healthmentioning
confidence: 99%
“…Other Nutraceuticals. Foods that contain nutrients that may help to boost immune function include Shiitake mushrooms (Dai et al 2015;Feeney et al 2014), Reishi mushrooms (Sanodiya et al 2009), aged garlic (Percival 2016), and echinacea (Block and Mead 2003;Karsch-Volk et al 2014). Besides vitamin D (the most important of all nutraceuticals for immune function), other vitamins that strengthen immunity include vitamin C and vitamin E (De la Fuente et al 1998;Moriguchi and Muraga 2000).…”
Section: Pay Attention To Physical Healthmentioning
confidence: 99%
“…After 12 weeks of oral supplementation, 80% of patients had enhanced cellular immunity, displaying elevated levels of plasma IFN-γ, IL-2, and IL-6, along with increased NK cell activity. Likewise, another clinical trial showed that supplementing the diet of 52 healthy, young males and females with 5g or 10g of dried shiitake ( Lentinula edodes ) mushrooms for 4 weeks improved the immune response by increasing cell proliferation and activation of γδ-T and NK-T cells [92]. Cytokine secretion patterns also changed significantly after consumption of the mushroom, with increased levels of IL-4, IL-10, and IL-1α and decreased levels of acute inflammatory cytokines such as macrophage inflammatory protein 1α (MIP1α).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…The effective compound of shiitake mushrooms is the thermolabile beta-glucan lentinan[167]. The raw shiitake mushrooms cause toxic dermatitis by reaction to lentinan thermolabile polysaccharide[168].…”
Section: Why the Cancer Cells Survive And How To Reject Them?mentioning
confidence: 99%